2001
DOI: 10.1159/000056567
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Multicystic Dysplastic Kidney in an Adult Woman

Abstract: We report a case of unilateral segmental multicystic dysplastic kidney (SMCDK) in an adult woman. A 42-year-old woman presented with abdominal distension and gross hematuria. The preoperative diagnosis was cystic renal cell carcinoma, and a radical nephrectomy was performed. Histopathologically, the resected kidney was SMCDK with severe hydronephrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The distinction between the 2 entities is, however, quite significant. Most of the 25 cases reported in the literature occurred in duplicated collecting systems, 94% of which were localized to the upper pole [1][2][3][4], which is consistent with the common occurrence of upper pole obstruction in duplicated systems. Only 5 cases of segmental MCDK in a single renal unit have been described.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The distinction between the 2 entities is, however, quite significant. Most of the 25 cases reported in the literature occurred in duplicated collecting systems, 94% of which were localized to the upper pole [1][2][3][4], which is consistent with the common occurrence of upper pole obstruction in duplicated systems. Only 5 cases of segmental MCDK in a single renal unit have been described.…”
Section: Discussionsupporting
confidence: 64%
“…The segmental form of MCDK is exceedingly rare, however, with only 25 cases reported [1][2][3][4]. Only 1 case of UPJ obstruction with hydronephrosis and segmental multicystic dysplasia in a kidney with a single collecting system has been reported [3].…”
mentioning
confidence: 99%
“…Our series of 6 patients brings the total number of reported cases of segmental MCDK to 35 [2,[4][5][6][7][8][9][10][11][12][13][14][15][16]. Several interesting observations arise from these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent authors have used the terms segmental or focal MCDK to describe this finding [4]. With only 28 pediatric cases [2,[4][5][6][7][8][9][10][11][12][13][14][15] and 1 adult case [16] reported, there is limited understanding of the presentation and natural history of segmental MCDK. The purpose of this study was to report our experience with the diagnosis of segmental MCDK, with particular emphasis on the initial manifestations, associated anomalies, imaging, management, and follow-up.…”
mentioning
confidence: 99%
“…However, we still have a limited understanding of segmental MCDK due to the limited number of studies and reports on this disease entity. 2,3,[7][8][9][10][11][12][13][14] Review of previous studies showed M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 2 that only 39 cases have been reported worldwide, and most were treated by routine surgical resection. Herein, we focused on conservative management of this relatively rare disease by investigation of involution, associated anomalies requiring surgery, and complications of segmental MCDK.…”
Section: Introductionmentioning
confidence: 99%